Pipeline Programs Can Support Reforms in Medical Education: A Cohort Study of Alabama's Rural Health Leaders Pipeline to Engage Community Leaders. Issue 4 (6th November 2020) - Wheat, John R.; Leeper, James D.
Abstract: Purpose: To demonstrate for county leaders the utility of rural pipelines to gain physicians and produce health professionals. Methods: This cohort study, 1993‐2018, aggregated 1, 051 students in the Rural Health Leaders Pipeline to their home counties (N = 67) to study the relationship between county participation in pipeline programs and outcomes of family physicians gained and health professionals produced. Additional county demographics were included. We conducted descriptive, bivariate, and multivariable linear regression analyses controlling for poverty, race, and rurality. Findings: All 67 Alabama counties participated with means of 9.6 Rural Health Scholars, 2.7 Rural Minority Health Scholars, 3.4 Rural Medical Scholars, 67% rural population, 29.7% Black population, and 21.5% under poverty. Best regression model for gaining family physicians included Rural Medical Scholars involved ( b = 0.24, P < .001) with R 2 0.30, indicating a county gained 1 family physician for 4 students. Best model for health professionals included Rural Health Scholars involved ( b = 0.20, P < .001) with R 2 0.31, indicating production of 1 health professional for 5 students. Best model for any professional included Rural Health Scholars involved ( b = 0.23, P < .001) with R 2 0.35, indicating 1 professional produced for 4 students. Conclusions: Rural pipeline programs can be useful tools in medical education reform to benefit counties with the gain of family physicians and production of health professionals. Local public officials could use these findings, eg, 1 family physician gained for every 4 students a county involved in the pipeline, to advocate that health professional education employ such pipelines.